Appropriateness of gastrointestinal prophylaxis use during hospitalization in patients with acute myocardial infarction: Analysis from the China Acute Myocardial Infarction Registry. Issue 1 (19th November 2020) - Shi, Wence; Ni, Lin; Yang, Jingang; Fan, Xiaoxue; Yu, Mei; Yang, Hongmei; Yu, Mengyue; Yang, Yuejin; ,
Abstract: Background: The current status of gastrointestinal prophylaxis (GIP) usage and its effects on hospitalized acute myocardial infarction (AMI) patients is not clear. We investigate the appropriateness of GIP usage and its relationship with clinical events in China. Hypothesis: Appropriate use of GIP is not associated with increased adverse outcomes. Methods: From January 2013 to September 2014, a total of 24 001 consecutive patients from 108 hospitals with AMI in China Acute Myocardial Infarction (CAMI) registry were analyzed. The appropriateness of GIP was evaluated using the current American College of Cardiology Foundation/American Heart Association (ACCF/AHA) and European Society of Cardiology (ESC) guidelines. The primary endpoint was in‐hospital gastrointestinal bleeding (GIB), while the secondary endpoints were in‐hospital and 2‐year follow‐up net adverse cardiovascular and cerebrovascular events (NACCE). Multivariate logistic regression analysis and Cox proportional hazard models were used to assess the effect of appropriate GIP. Results: There were 16 413 (68.38%) AMI patients co‐medicated with GIP. Among 108 involved hospitals, only 35 (32.4%) hospitals prescribed more than 50% appropriate GIP. Totally, 59.7% (14 340) AMI patients received inappropriate GIP. Inappropriate GIP use was independently associated with use of GPIIb/IIIa receptor inhibitor and primary percutaneous coronary intervention (PCI). Moreover, appropriate GIP use was associated with decreased GIB risk (OR: 0.692, 95% CI: 0.507‐0.944, P = .0202) during hospitalization, while not with increased in‐hospital and 2‐year follow‐up NACCE. Conclusion: The use of GIP is prevalent in patients with AMI in China but only 40% of hospitalized patients received appropriate GIP. Appropriate prophylactic therapy was associated with decreased GIB risk during hospitalization.